SOLUSI PENYELESAIAN PERCERAIAN YANG TIDAK DICATAT - St. Syahruni Usman (IAIN Ambon, 2017)
No lasting marriage last forever, until death couples. Many couples who end a marriage through divorce. In this connection, ideally divorce must be registered and based on court decisions. However, many divorces that occur in society without noting the authorities. The cause of the divorce were not recorded, are: 1) the marriage has not been/is not registered at the Office of Religious Affairs; 2) the absence of costs in applying in the Religious; and 3) do not know the law that applies (legally blind). Solutions to divorce is not recorded, are 1) the legal process of divorce and divorce contested divorce preceded ithbat marriage to marriage is not recorded; and 2) to apply or if it is not able to divorce lawsuit filed by case basis without cost. Keywords: divorce settlement, not recorded